PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA SURABAYA PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA SURABAYA - SUFIAH, (Jurnal Akuntansi AKUNESA, 2017)
Thisistudy is aimed toiexamine theieffectiofitaxpayer’s internal factors which are religiosity and taxpayer awareness, also the taxpayer’s external factors which are service tax authorities, and tax penalties on taxpayer’s individual compliance. The type of this study is classified as a quantitative research. The population inithis studyiis Surabaya’s individualitaxpayer. Theiselection of the sample used convenience sampling method. Data collection method used is by using questionnaire. Analysis used in this study is using multiple regression analysis which the result shows that religiosity, taxpayer awareness, serviceitax authorities, and tax penalties has positive affect on taxpayer’s individual compliance. Keywords: tax compliance, religiosity, taxpayer awareness, service tax authorities, tax penalties